Variations in Parameters of Hepatotoxicity Induced by Anti TB Treatment with Comorbid Acute Viral Hepatitis - Asma Kazi, Aisha Aziz, Fatima Arshad, Samina Karim, Rao Salman Aziz, Maheen Rana (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives & background: Drug-induced hepatotoxicity (DIH) is a common side effect of anti-TB drugs. Acute viral hepatitis (AVH) may be confounded with chronic alcoholic hepatitis clinically, biochemically, and histologically (CAH). Place of Study: Rashid Latif Medical College Lahore Duration of Study: March 2019 to January 2021 Methods: This prospective research examined the effect of acute viral hepatitis as a contributing and confounding factor in patients with normal baseline liver function who acquired acute hepatitis while taking short-course anti-TB medication. All acute hepatitis patients’ blood was analysed for hepatitis A, B, C, and E markers. Results: In 12 of 80 TB patients who developed viral hepatitis, the hepatitis E virus was present. Indicators of acute viral hepatitis included a delayed onset of acute hepatitis significant increases in aspartate aminotransferase (AST) and alanine aminotransferase (ALT), and a longer period for abnormal levels to normalise. Conclusions: According to our statistics, 15% of anti-TB hepatotoxic patients had AVH. Before attributing the hepatotoxic impact of anti-TB medications to DIH patients, viral hepatitis should be evaluated and ruled out in all endemic-area patients.